Key determinants of bank profitability in Indonesia, Malaysia, Singapore &Thailand. - Wong, Wei. (2009)
Profitability is a major criterion for evaluating bank performance. Massive literature has been done on banks in Europe and North America on this subject. However, few studies have been performed on banks in the ASEAN region. Our research aims to explore whether profitability determinants that have proven influential in Western countries also apply to the ASEAN context. These determinants include Capital, Liquidity, Concentration, Interest rate, Inflation, Ownership and Market Growth. An additional determinant, Strategic Response Quotient, propounded by Dr John Vong (1994) is also included in this study. Two measures of bank performance, Return on Assets and Return on Equity, are evaluated in this study. Analysis is performed based on a sample database comprising 33 banks from Indonesia, Malaysia, Singapore and Thailand. The Multiple Linear Regression method is used to determine the relationships between bank performance and the key determinants.